Mechanized: Transforming Africa’s agriculture value chains - Malabo Montpellier Panel; Glatzel, Katrin; Tankari, Mahamadou Roufahi; Demmler, Kathrin (International Food Policy Research Institute, 2018)
The current report—Mechanized: Transforming Africa’s Agriculture Value Chains—summarizes the findings of a systematic analysis of what countries at the forefront of progress in mechanization have done right. It analyzes which policy decisions were taken and which interventions were implemented to substantially increase the uptake of mechanization. The report takes a broad perspective on mechanization, including technologies along the entire value chain and how they relate to agricultural development and job creation. The report shows what can be done to sustainably mechanize agriculture to increase production and enhance value addition across value chain segments. The set of policies and practices that are identified, if brought to scale, could have significant impact on agricultural transformation in Africa. The report provides a roadmap for African governments to take concerted action to deliver on the growth and transformation targets set out by the Malabo Declaration and the Sustainable Development Goals.